PERANCANGAN LOGO DAN MEDIA PROMOSI PANTAI LUMBUNG TULUNGAGUNG MENGGUNAKAN TEKNIK FOTOGRAFI LANDSCAPE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Mardha, Harel Laisa; Budiardjo, Hardman; Adrianto, Yosef Richo (Jurnal Art Nouveau, 2016)
The purpose of designing the logo and promotional media Lumbung Beach is to make a new tourist attraction in Tulungagung. The research was conducted with qualitative methods of doing interviews, documentation, observation and literature study to get the data used to support the manufacture of logo design concepts and media promotion. The concept in this study was obtained from the SWOT analysis, STP, and USP then the adjective derived dikerucutkan back so "cozy" was elected to the keywords in this study. In the Oxford dictionary of English "cozy" has the meaning that is interesting and fun. In such case, this concept seems to be pleasant to have a close relationship with travel Lumbung Beach Tulungagung. So in this design to be visualized creatively with the object that looks nice is the large rock icon on the coast, and "Stone Barn" which can be climbing in travel Lumbung Beach. Results of designing the logo and media campaign is to make the beach Lumbung as a major tourist destination in Tulungagung.Â Keywords : Logo , Media Promotion , Lumbung, Tulungagung